2021
DOI: 10.3390/ijms22041981
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Cellular Roles of SMUG1 in Genome Maintenance and Cancer

Abstract: Single-strand selective monofunctional uracil DNA glycosylase 1 (SMUG1) works to remove uracil and certain oxidized bases from DNA during base excision repair (BER). This review provides a historical characterization of SMUG1 and 5-hydroxymethyl-2′-deoxyuridine (5-hmdU) one important substrate of this enzyme. Biochemical and structural analyses provide remarkable insight into the mechanism of this glycosylase: SMUG1 has a unique helical wedge that influences damage recognition during repair. Rodent studies sug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Endogenously, hmdU accumulates in genomic DNA through several ways, including loss of the glycosidase DNPH1, which hydrolyzes hmdU, hydroxylation of thymidine by TET dioxygenases, oxidation of thymidine by reactive oxygen species, and deamination of 5-hydroxymethylcytosine (5hmC) by cytidine deaminase (Fugger et al, 2021;Olinski et al, 2016;Pfaffeneder et al, 2014;Teebor et al, 1984). Although not cytotoxic on its own, cells become sensitive to genomic hmdU when the uracil glycosylase SMUG1 hydrolyzes the base to create an abasic site (Fugger et al, 2021;Raja and Van Houten, 2021;Taglialatela et al, 2021) To separate the roles of replication fork protection and ssDNA gap suppression in the response to hmdU, we rescued both pathways by depleting SMARCAL1 and PRIMPOL, respectively. We found that PRIMPOL-mediated gap formation is responsible for hmdU sensitivity and that this was specifically due to gap formation at abasic sites generated by SMUG1.…”
Section: Primpol-dependent Ssdna Gaps and Sensitivity To Hmdumentioning
confidence: 99%
“…Endogenously, hmdU accumulates in genomic DNA through several ways, including loss of the glycosidase DNPH1, which hydrolyzes hmdU, hydroxylation of thymidine by TET dioxygenases, oxidation of thymidine by reactive oxygen species, and deamination of 5-hydroxymethylcytosine (5hmC) by cytidine deaminase (Fugger et al, 2021;Olinski et al, 2016;Pfaffeneder et al, 2014;Teebor et al, 1984). Although not cytotoxic on its own, cells become sensitive to genomic hmdU when the uracil glycosylase SMUG1 hydrolyzes the base to create an abasic site (Fugger et al, 2021;Raja and Van Houten, 2021;Taglialatela et al, 2021) To separate the roles of replication fork protection and ssDNA gap suppression in the response to hmdU, we rescued both pathways by depleting SMARCAL1 and PRIMPOL, respectively. We found that PRIMPOL-mediated gap formation is responsible for hmdU sensitivity and that this was specifically due to gap formation at abasic sites generated by SMUG1.…”
Section: Primpol-dependent Ssdna Gaps and Sensitivity To Hmdumentioning
confidence: 99%
“…To further verify the gene expression signatures before and after PARPi treatment, several gene expression levels were analyzed using qPCR with specific primers. FEN1 and SMUG1 are highly expressed and regarded as promising biomarkers in OC 14 , 15 . Therefore, changes in the expression of FEN1 and SMUG1 , as well as uracil-DNA glycosylases encoding gene UNG , after PARPi treatment were also evaluated to identify potential drug targets.…”
Section: Resultsmentioning
confidence: 99%
“…Single-strand selective monofunctional glycosylase (SMUG1) works to remove 5-hmdU, uracil, 5-fluorouracil, and oxidized thymidine derivatives from DNA. The name is a misnomer, as SMUG1 can recognize and process substrates on both single-stranded and double-stranded DNA with almost equal activities [ 65 ]. The enzymatic activity of SMUG1 on nucleosomes has been previously studied by the Delaney group, and SMUG1 activity on lesions within nucleosomes decreases three- to nine-fold [ 17 ].…”
Section: Role Of Uv-ddb In 5-hydroxymethyl-2-deoxyuridine Repairmentioning
confidence: 99%